1996
DOI: 10.1088/0953-8984/8/29/005
|View full text |Cite
|
Sign up to set email alerts
|

A thermodynamic and structural analysis of selenium - tellurium melts

Abstract: The thermodynamic properties of the selenium - tellurium system are analysed in terms of a novel regular solution model with multiple connectivity. The model is an extension of the regular solution model that discriminates between two forms of tellurium atom according to their connectivity (number of first neighbours). In the resulting ternary system, the chemical equilibrium between these two forms of tellurium is taken into account. The model can be solved in either the Bragg - Williams or the quasi-chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

1998
1998
2003
2003

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…The enthalpy of mixing, negative at low temperature, becomes positive at higher temperatures. By means of suitable thermodynamic modeling, Amzil et al [7] suggested that the structural changes in liquid tellurium were responsible for the observed phase separation tendency in the liquid. Their thermodynamic model is based on the assumption that the number of first neighbours of the tellurium atoms in the melt varies from 2 at low temperature to 3 at higher temperatures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The enthalpy of mixing, negative at low temperature, becomes positive at higher temperatures. By means of suitable thermodynamic modeling, Amzil et al [7] suggested that the structural changes in liquid tellurium were responsible for the observed phase separation tendency in the liquid. Their thermodynamic model is based on the assumption that the number of first neighbours of the tellurium atoms in the melt varies from 2 at low temperature to 3 at higher temperatures.…”
mentioning
confidence: 99%
“…-Looking at the partial coordination numbers, this sharp drop is essentially due to the tellurium contribution, whereas sulphur remains essentially twofold coordinated, with a possible tendency to lower this number of first neighbours on the sulphur-rich side and at high temperature, due to the breaking of the chains and rings in the structure. Bearing in mind both experimental and theoretical studies on liquid tellurium [2,3] and on selenium-tellurium melts [7,15], these results can be interpreted in the following way. Neglecting chain-breaking effects, pure liquid tellurium tends towards a threefold coordinated state at high temperatures, with two intrachain bonds and a certain number of bonds (on average 1) bridging the chains.…”
mentioning
confidence: 99%
“…Pour bien cadrer cette démarche, il faut préciser qu'on ne cherche pas à prédire les grandeurs thermodynamiques à partir des données de structure mais plutôt à montrer que ces dernières sont compatibles avec l'existence d'une séparation de phases. Les détails de l'établissement des diverses fonctions thermodynamiques ne seront pas rappelés ici mais tous les calculs peuvent être trouvés dans la référence [33]. Les principaux résultats portant sur les grandeurs thermodynamiques sont rappelés ici.…”
Section: Principe Des Méthodes D'affinementunclassified
“…The overall behaviour of thermodynamic properties has been explained by assuming two forms of a Se-Te alloy coexisting in thermal equilibrium, the fraction of which changes in a rather narrow in the composition-temperature (x − T ) plane. 12,13) With a set of plausible parameters the models could reproduce steeply range 473 quantitatively the thermodynamic properties as a function of temperature and composition. Furthermore in the course of calculations, it was shown that the structural change causes weak tendency towards instability of a mixture: the concentration-concentration fluctuations, S cc (0), in the limit of long wave length develops along the T * − x curve.…”
Section: §1 Introductionmentioning
confidence: 99%
“…24) The small negative value of the interchange parameter implies that the interaction between Se and Te atoms is slightly attractive in the low temperature form and Se-Te alloy has weak tendency of chemical ordering. Combining equations (13) and (14), we have,…”
Section: §1 Introductionmentioning
confidence: 99%